Analisis Kepuasan Pengguna Sistem E-commerce Penjualan Pakaian sebagai Media Pendukung Pembelajaran Menggunakan Metode EUCS - Johanes Mula Febrian Sihombing; Muhammad Najamuddin Dwi Miharja; Nanang Tedi Kurniadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The development of digital technology in education has encouraged the use of e-commerce systems as learning support media, making user satisfaction evaluation essential to ensure system effectiveness. This study aims to measure the level of user satisfaction with an e-commerce system utilized in digital learning activities. The research employed a quantitative approach using the End-User Computing Satisfaction (EUCS) method, which consists of five dimensions: content, accuracy, format, ease of use, and timeliness. Data were collected through questionnaires distributed to 61 respondents and analyzed using validity testing, reliability testing, mean analysis, and correlation analysis. The results indicate that all questionnaire items are valid and reliable, while all EUCS dimensions obtained mean scores above 4.000, indicating a high level of user satisfaction. The highest mean values were found in the accuracy and ease of use dimensions (4.268), while correlation analysis revealed that the strongest relationship occurred between the content and format dimensions with a correlation coefficient of 0.726. This study contributes by providing empirical evidence regarding user satisfaction with the use of e-commerce systems as learning media and by identifying the relationships among EUCS dimensions that influence user perceptions. In conclusion, the e-commerce system has successfully met user needs and effectively supported digital learning activities.